2007
DOI: 10.1038/modpathol.3800833
|View full text |Cite
|
Sign up to set email alerts
|

Clonal relationships between epidermotropic metastatic melanomas and their primary lesions: a loss of heterozygosity and X-chromosome inactivation-based analysis

Abstract: Loss of heterozygosity (LOH) has previously been demonstrated at multiple chromosome microsatellites in primary and metastatic melanomas. Epidermotropic metastases of melanoma are unique in their varied histopathologic appearance, which can mimic a primary lesion. Our objective was to compare LOH profiles in primary and epidermotropic metastatic melanoma to delineate their clonal relationship. We examined the pattern of allelic loss in the primary melanomas of nine patients in addition to the 21 corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
(53 reference statements)
2
12
0
Order By: Relevance
“…Trent et al demonstrated that melanoma lines directly introduced with a normal copy of chromosome 6 lost their ability to form tumors in nude mice, and the loss of chromosome 6 from melanoma microcell hybrids resulted in reversion to tumorigenicity of these cells(Trent et al , 1990). High frequency of loss of heterozygosity(LOH) of chromosome 6q has also been reported in melanoma lines and tissues(Bahrami et al , 2007; Fujiwara et al , 1999; Stark and Hayward, 2007). However, it still remains unclear which key genes are specifically involved in melanoma progression in the 6q21-22 region of melanomas.…”
Section: Discussionmentioning
confidence: 98%
“…Trent et al demonstrated that melanoma lines directly introduced with a normal copy of chromosome 6 lost their ability to form tumors in nude mice, and the loss of chromosome 6 from melanoma microcell hybrids resulted in reversion to tumorigenicity of these cells(Trent et al , 1990). High frequency of loss of heterozygosity(LOH) of chromosome 6q has also been reported in melanoma lines and tissues(Bahrami et al , 2007; Fujiwara et al , 1999; Stark and Hayward, 2007). However, it still remains unclear which key genes are specifically involved in melanoma progression in the 6q21-22 region of melanomas.…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence of multiple lesions in the vicinity of the primary melanoma site also provides compelling clinical evidence for metastases. However, when clinicopathological correlation fails to elucidate the primary versus metastatic nature of a lesion, molecular studies may be needed to facilitate more accurate staging …”
Section: Discussionmentioning
confidence: 99%
“…However, variable patterns within the same case indicate that, while some epidermotropic metastatic melanomas are clonally related to the primary, others are of independent origin. [13]…”
Section: Discussionmentioning
confidence: 99%